Romance of commander Moreno : Music of oral tradition, history and education - López Fernández, Carme (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In this article we treat the “romance do Comandante Moreno” as part of the music of Galician oral tradition and of the historical memory in relation to the Spanish Civil War. Methodologically we work with ethnomusicological analysis that focuses on musical, literary and contextual parameters, in addition to working with bibliographic and audiovisual references. Thus, we find characteristics of the music of Galician tradition and a concise description of the facts, this romance being a reliable witness to the murders that occurred in 1937 and, therefore, an element with educational opportunities for the creation of interdisciplinary projects.